استخدام التيارات عالية التردد في تسخين الأسطوانات الفولاذية - علي عدنان (Latakia University Journal -Engineering Sciences Series, 2019)
تستخدم التيارات عالية التردد بشكل واسع في الصناعات المعدنية وخاصةً لتسخين الأسطوانات والصفائح المعدنية تحريضياً ، لذلك لابد من إعداد نموذج رياضي للحسابات الكهروديناميكية والحرارية . في هذا البحث تم دراسة مسألة تسخين الأسطوانات المعدنية الفولاذية الطويلة ذات القطر الصغير والتي تتحرك باتجاه محور ملف التسخين ( الملف الذي يمرر التيار عالي التردد ويولد الحقل المغناطيسي الذي يقوم بدور التسخين). كما تم حساب المقاومة غير الخطية للأسطوانات المراد تسخينها بالإحداثيات الأسطوانية, باعتبار أن المحور X يتطابق مع محور الأسطوانة، آخذين بعين الاعتبار دراسة التأثير الحراري للسماحية المغناطيسية وعلاقتها بعمق تسرب الموجة المغناطيسية في معدن الأسطوانة. Higher Frequency Currents are widely used in metallic industries particularly for inductive heating of the metal cylinders and plates. Therefore its highly necessary to prepare a mathematical model for the thermal and electro-dynamic calculations. In this paper, we studied the problem of heating the long steel, metallic cylinders of small diameter, which moves towards the axis of heating coil (the coil in which passes the higher frequency current and generates the magnetic field that performs the function of heating ). We Calculated the nonlinear resistance for the cylinders to be heated by cylindrical coordinates since the axis (X) corresponds with the axis of the cylinder, taking into consideration studying the thermal effect of magnetic tolerance, and its relation with the depth of magnetic wave leak in the cylinder metal.